The forgotten forest : on thinning, retention, and biodiversity in the boreal forest - Klein, Julian (2020)
Fennoscandia has had a long history of intensive forest management. It can therefore be regarded a trial zone for other boreal regions which are still largely unaffected by forestry. In Fennoscandia, forestry has resulted in many threatened species and methods that maintain biodiversity have therefore been called for. Retention forestry, where parts of the forest and structural elements key to biodiversity are retained, have here been introduced to the final felling stage. However, for intermediate stages such as forest thinning, few such methods have been suggested and none have been tested experimentally. I therefore performed empiric and experimental studies investigating the effects of current and alternative forest thinning routines on biodiversity and the breeding success and occurrence of singular species, in two study locations in Sweden. I show that conventional thinning reduces the forests structural complexity and has a strong influence on the species composition and richness of forest-dwelling birds and epiphytic lichens in young managed forests typical for Fennoscandia. This influence was largely negative for forest-dwelling birds at least in the short term, but under certain conditions positive for epiphytic lichens. Adjusting conventional forest thinning towards a retention forestry approach will according to my thesis likely result in a higher biodiversity in these forests compared to what is practice today. This can be achieved if (i) either the understory vegetation below 3-5 m above ground on the whole stand or (ii) entire plots of ca. 1 ha are retained, (iii) an even and rich tree species composition is re-established, and (iv) more large-diameter trees are spared. The Siberian jay is considered indicative of the effect of thinning on bird species relying on a complex forest vegetation. In a habitat suitability model, I provide detailed spatial information on where thinning can increase or decrease the jay’s breeding success, based on the distance of a forest to human settlements. These ...